The Role of Adiwiyata Cadres in Fostering Students’ Environmental Awareness Character as Manifestation of Social Capital in Madrasah - Nabila Rahma Shabrina; Dasim Budimansyah; Dwi Iman Muthaqin (Urwatul Wutsqo)
This study focuses on the role of Adiwiyata Cadres in developing environmental awareness as a form of students' social capital at MTsN 10 Tasikmalaya. The background of this research stems from the low quality of the environment in Indonesia, particularly in Tasikmalaya Regency, which is caused by a lack of public awareness regarding the importance of environmental preservation. This study aims to describe the implementation, impact, as well as the challenges and efforts made by Adiwiyata Cadres in Islamic junior high schools in shaping students' environmentally caring character. This research employs a qualitative approach with a case study method. Data collection techniques include participatory observation, in-depth interviews, and document analysis. The findings indicate that Adiwiyata Cadres at MTsN 10 Tasikmalaya internalize Islamic values. Their activities positively influence the development of students' environmental awareness and strengthen the religious-based social capital within the school environment. The obstacles faced by the Adiwiyata Cadres come from both internal and external cadre management. This study supports the idea that Adiwiyata Cadres must be continuously developed as integral to character education and sustainable education in Islamic-based junior secondary schools